Interior Dissemination of The Showroom of The Technopark Building of The UPN Veteran Jawa Timur - N. Anggriani; D. Agustin; W. D. Susanti (Nusantara Science and Technology Proceedings)
UPN Veteran Jawa Timur is a state university in Surabaya with a state defense character and excels in the Tri Dharma of Higher Education. More than 150 effective products have been produced by researchers and have been used by the public. However, currently the arrangement of appropriate products is not well organized and maximized and does not have representative showrooms. FAD as a faculty that has superior products of interior design showrooms will conduct research with the title of Interior Dissemination of Exhibition Room of UPN Veteran Jawa Timur Technopark Building. This research is expected to be able to disseminate the showroom interior arrangement technology that reflects the country's defense character as a characteristic of UPN to exhibit various appropriate products from the research activities and community service of UPN Veteran Jawa Timur so that it will ultimately improve the image and excellence of veteran UPN Jawa Timur. A well-arranged interior arrangement can increase visitors' comfort in seeing the tool. The method used in this study is observation, data collection tools and design processes. In the design process used behavioral methods in this case is the behavior of visitors in the area of the showroom at the Technopark Building UPN Veteran Jawa Timur.